ANALYSIS OF CASH, DEBT AND PROFITABILITY AT PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Kalsum, Umi; Farisi, Salman; Muslim, Muslim; Meliandani, Winda (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
The purpose of this study was to determine and analyze cash, debt and profitability at PT. Perkebunan Nusantara III (Persero) Medan period 2013-2018. This research method uses a descriptive approach with primary and secondary data sources. The data collection technique in this study used a documentation study. The results showed that cash and debt were not optimal in increasing the profitability of ROI (return on investment) and ROE (return on equity). Where cash has decreased every year because the company does not contribute to the company's wealth (profit) to cash which is feared that cash will not be able to finance its debts.PT. Perkebunan Nusantara III Medan in 2013-2018 experienced a significant increase, where the increasing debt will affect the company's profitability.